الاستراتيجية التوجيهية للخطاب - شعر الحرب في الأندلس أنموذجاً - مصطفى, د. روشن عبدالستار (Sulaimani Journal for Humanities, 2021)
The Discourse has functions and strategies that cannot be overlooked or ignored. The poetic text can be treated as a discursive model because of its performance of the discourse functions and strategies including the guiding strategy. The poetry of war in Andalusia was chosen as a model for determining the guiding strategy to provide an element of suitability in it. In this research the theoretical framework of the concept of discourse and the guiding strategy of the discourse were defined. Through a theoretical introduction we have selected themes and text of war poetry that are appropriate for the guiding discourse. Therefore the nature of the research necessitated dividing it into three sections after the introduction. The first topic was on the discourse of jihad the second section was on the discourse of warning and alert the third topic was on shouting. We followed a descriptive and analytical approach in monitoring the appropriate poetic discourses and the analyzing them according to the rules of the directive discourse.